2009
DOI: 10.1007/s11458-009-0004-0
|View full text |Cite
|
Sign up to set email alerts
|

Properties of partially hydrolyzed PAN fibers

Abstract: The properties of base PAN (polyacrylonitrile) fibers and their partially hydrolyzed PAN-COOH fibers were characterized by means of a Fourier transform infrared spectrophotometer, elemental analyzer, specific surface area analyzer etc. The main factors that can affect the strength of the base PAN fibers and how the hydrolysis reaction happens in alkaline conditions are discussed. Acidic hydrolyzed PAN-COOH fibers, having a strength of 9.6 cN/dtex, capacity of 0.26 mmol/g, BET area of 0.58 m 2 /g (calculated on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 3 publications
(3 reference statements)
0
4
0
Order By: Relevance
“…The control PAN fibre represented its primary functional peak at 2240 cm −1 attributed to the C≡N (nitrile group) and the secondary peaks at 1470 cm −1 and 2930 cm −1 are credited to the bending and stretching vibration of methylene groups, correspondingly 26 . The other functional groups have been found at 1070 cm −1 , 1350 cm −1 , and 1730 cm −1 because of the presence of C–CN groups, stretching of C–H in CH groups, and specific stretching and absorption of C=O in COOH groups, respectively 35 38 . For the WP hybrid fibres prepared with different weight ratios of wool content, it can be seen that amide-II (1530 cm −1 ), amide-A (3280 cm −1 ) groups from the wool powder have been diminished, which might be due to the proper dissolution of the wool powder in the alkaline organic solution 39 .…”
Section: Resultsmentioning
confidence: 99%
“…The control PAN fibre represented its primary functional peak at 2240 cm −1 attributed to the C≡N (nitrile group) and the secondary peaks at 1470 cm −1 and 2930 cm −1 are credited to the bending and stretching vibration of methylene groups, correspondingly 26 . The other functional groups have been found at 1070 cm −1 , 1350 cm −1 , and 1730 cm −1 because of the presence of C–CN groups, stretching of C–H in CH groups, and specific stretching and absorption of C=O in COOH groups, respectively 35 38 . For the WP hybrid fibres prepared with different weight ratios of wool content, it can be seen that amide-II (1530 cm −1 ), amide-A (3280 cm −1 ) groups from the wool powder have been diminished, which might be due to the proper dissolution of the wool powder in the alkaline organic solution 39 .…”
Section: Resultsmentioning
confidence: 99%
“…The control PAN signified its functional peak at 2240 cm −1 , 1470 cm −1 , and 2930 cm −1 which are ascribed to the C≡N (nitrile group), bending and stretching vibration of methylene groups, correspondingly ( Supplementary Figure S3a ) [ 34 ]. The other functional groups have been found at 1070 cm −1 , 1350 cm −1, and 1730 cm −1 due to the C-CN groups, stretching of C-H in CH groups, stretching and absorption of C=O in COOH groups, respectively ( Supplementary Figure S3a ) [ 35 , 36 , 37 , 38 ]. On the other hand, the typical peaks of GO can be seen from 950 cm −1 to 1450 cm −1 , derived from the occurrence of C–O bonds of epoxy groups, hydroxyl groups, and other C-OH vibrations of carboxyl groups, with peaks at 1628 cm −1 , 1730 cm −1 , and 3280 cm −1 confirming the presence of C=C, C=O, and -OH groups, correspondingly ( Supplementary Figure S3b ) [ 19 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…Chen et al reported the properties of the partially hydrolyzed PAN. The difference in strength and thermal stability of PAN fiber with their partially hydrolyzed PAN‐COOH fibers was studied by this group . In 2011, Kim and co‐workers studied the increase in effect of alkaline hydrolysis and nitrile conversion kinetics using high‐resolution solid state 13 C NMR spectroscopy on commercially available hollow PAN ultrafiltration membrane (UF) surface…”
Section: Nitrile Group Modifications In Polymersmentioning
confidence: 99%